Didymodon tomaculosus (Blockeel) M.F.V.Corley, new to the moss flora of Turkey and Asia (Bangladesh Journal of Botany, 2013)
Didymodon tomaculosus (Blockeel) M.F.V.Corley is reported for the first time from Turkey, bringing the total number of Didymodon species known from Turkey to 19. D. tomaculosus is also reported first time to the moss flora of Asia. It is a very rare species and was known only from British Isles and south of Germany. Description, illustrations and diagnostic characters of the species are given, together with notes on its ecology. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13445 Bangladesh J. Bot. 41(2): 177-179, 2012 (December)